Weed management of jute (Corchorus olitorius) by soil solarisation* - GHORAI, A K (The Indian Journal of Agricultural Sciences, 2011)
Soil solarisation by clear and black polyethylene (200- 400 gauge) raised the soil temperature up to 54OC in 0-5 cm soil profile at 2 PM over 38 to 40 OC under bare soil cultivation. It killed the sprouted grass, broad leaved and sedges weeds and reduced the weed load in jute field. Clear polyethylene reduced weed emergence by 45-78% at 21 days after jute emergence. Solarisation by black polyethylene and mixed cropping red amaranth in jute reduced weed emergence by 56 to 93% at 21 days after emergence. Solarisation by clear and black polyethylene produced 4 429 to 5 083 kg and 4 900 kg jute fibre/ha, respectively over 3 515 kg/ha from manually weeded plots. Quizalofop-ethyl(5% EC) @ 45 g a.i./ba (DT,, < Id) at 15 days after emergence and one hand weeding produced 4 640 kg fibre/ha. Soil soalrisation is a safe method, gave higher fibre yield over the manual and chemical weeding processes. It can be practiced provided cost of polyethylene is low and its safe disposal is ascertained.